Systemic lupus erythematosus variants modulate the function of an enhancer upstream of TNFAIP3 - Pasula, Satish; Gopalakrishnan, Jaanam; Fu, Yao; Tessneer, Kandice L.; Wiley, Mandi M.; Pelikan, Richard C.; Kelly, Jennifer A.; Gaffney, Patrick M. (Frontiers in Genetics, 2022)
TNFAIP3/A20 is a prominent autoimmune disease risk locus that is correlated with hypomorphic TNFAIP3 expression and exhibits complex chromatin architecture with over 30 predicted enhancers. This study aimed to functionally characterize an enhancer ~55kb upstream of the TNFAIP3 promoter marked by the systemic lupus erythematosus (SLE) risk haplotype index SNP, rs10499197. Allele effects of rs10499197, rs58905141, and rs9494868 were tested by EMSA and/or luciferase reporter assays in immune cell types. Co-immunoprecipitation, ChIP-qPCR, and 3C-qPCR were performed on patient-derived EBV B cells homozygous for the non-risk or SLE risk TNFAIP3 haplotype to assess haplotype-specific effects on transcription factor binding and chromatin regulation at the TNFAIP3 locus. This study found that the TNFAIP3 locus has a complex chromatin regulatory network that spans ~1M bp from the promoter region of IL20RA to the 3’ untranslated region of TNFAIP3. Functional dissection of the enhancer demonstrated co-dependency of the RelA/p65 and CEBPB binding motifs that, together, increase IL20RA and IFNGR1 expression and decreased TNFAIP3 expression in the context of the TNFAIP3 SLE risk haplotype through dynamic long-range interactions up- and downstream. Examination of SNPs in linkage disequilibrium (D’=1.0) with rs10499197 identified rs9494868 as a functional SNP with risk allele-specific increase in nuclear factor binding and enhancer activation in vitro. In summary, this study demonstrates that SNPs carried on the ~109kb SLE risk haplotype facilitate hypermorphic IL20RA and IFNGR1 expression, while suppressing TNFAIP3 expression, adding to the mechanistic potency of this critically important locus in autoimmune disease pathology.